1973
DOI: 10.1136/bmj.1.5847.193
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Hyperreactivity to Prostaglandin F2  and Histamine in Patients with Asthma

Abstract: SummaryThe influence on airway conductance of inhaled aerosols of prostaglandin F2c (PGF2oc), histamine, and prostaglandin E2 (PGE2) was studied in 10 patients with spirometrically reversible bronchial asthma and in 10 healthy subjects with no history of lung disorder. Both groups responded with bronchoconstriction after inhalation of PGF,oc but the asthmatic patients were about 8,000 times more sensitive to the compound than were the healthy controls. In the patients, but not in the controls, PGF2x often caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1
2

Year Published

1974
1974
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(60 citation statements)
references
References 24 publications
6
51
1
2
Order By: Relevance
“…Asthmatics have been observed to be hyperreactive to inhalation of PGF2, (26) and histamine (27). However, the present finding that histamine, PGF2a, and LTC4 had the same absolute and relative contractile potency in bronchi from asthmatics as in bronchi from nonasthmatics (3) would seem to indicate that hyperreactivity is an in vivo phenomenon due to factors other than hypersensitivity of the bronchial smooth muscle to the agonists.…”
Section: )contrasting
confidence: 54%
See 1 more Smart Citation
“…Asthmatics have been observed to be hyperreactive to inhalation of PGF2, (26) and histamine (27). However, the present finding that histamine, PGF2a, and LTC4 had the same absolute and relative contractile potency in bronchi from asthmatics as in bronchi from nonasthmatics (3) would seem to indicate that hyperreactivity is an in vivo phenomenon due to factors other than hypersensitivity of the bronchial smooth muscle to the agonists.…”
Section: )contrasting
confidence: 54%
“…The major cyclooxygenase product, TXB2, had a specific radioactivity of [25][26][27][28][29][30][31][32][33][34][35] pCi/pmol, as compared with 56 pCi/pmol for the added exogenous substrate. The mono-HETEs showed a specific radioactivity of 4-10 pCi/pmol, indicating a lower, but still significant, incorporation of exogenous substrate into these lipoxygenase products.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested that hypersensitivity to endogenous PGF2a may significantly contribute to increased airways resistance and that the local release of PGF2a might explain the precipitation of the asthmatic attack by a wide variety of stimuli. A recent study (Smith, Cuthbert & Dunlop, 1975) has confirmed the hypersensitivity of asthmatics to PGF2a inhalation but has shown a very marked individual variation, some asthmatics being no more sensitive than healthy subjects while other showed a similar hypersensitivity to that reported by Mathe et al (1973). This variation in sensitivity was not correlated with any particular feature of the nature or duration of the asthma or its treatment.…”
Section: Prostaglandins and Asthmasupporting
confidence: 53%
“…Secondly, since indomethacin inhibits the biosynthesis of both E and F prostaglandins it is assumed that the effect of a reduction in the bronchoconstrictor PGF2., is not simply offset or otherwise influenced by a comparable reduction in the bronchodilator PGE2. It is true that E prostaglandins can occasionally cause bronchoconstriction (Cuthbert, 1969;Mathe et al, 1973) but this problem will probably not be resolved until specific inhibitors of the synthesis or action of the F prostaglandins are developed. The availability of such compounds will also resolve the important question whether a specific reduction or antagonism of PGF2.…”
Section: Prostaglandins and Asthmamentioning
confidence: 99%
“…The potent bronchoconstrictor effect of many prostaglandins has suggested their participation in the pathogenesis of bronchial asthma (Mathe et al, 1973). PGE2 and PGI2 have been usually considered to counteract the effects of bronchoconstrictor prostaglandins.…”
Section: Discussionmentioning
confidence: 99%